PET/CT Imaging in Oncology: Clinical Updates and Perspectives - Piccardo, Arnoldo; Fiz, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the most recent advances in PET/CT imaging within the field of oncology. These innovations include studies on novel or experimental tracers, such as [18F]FES for the imaging of advanced breast cancer and [68Ga]Ga-Nitroimidazole for visualizing hypoxic tumour components; research on new radiopharmaceuticals represents, in fact, one the most important study fields of PET research. Advanced image analysis, such as radiomics, is also featured in this reprint; this method has been applied to both traditional nuclear medicine clinical issues, such as thyroid nodules, as well as in the setting of new therapeutic approaches, such as CAR-T cell therapy. Finally, the theranostic implications of PET radiotracers and the diagnostic processes of rare tumours are explored in this reprint.